"I am more engaged in writing": Promoting EFL Students’ Writing Skills through Project-Based Learning - Hidayat, Wardatul Layly; Rojabi , Ahmad Ridho (SALEE: Study of Applied Linguistics and English Education, 2025)
Writing remains one of the most demanding productive skills for English as a Foreign Language (EFL) students. To address this challenge, Project-Based Learning (PBL), a student-centered instructional approach, has gained attention for its potential to enhance student engagement and writing performance. This qualitative case study explored: (1) the instructional steps used in implementing PBL in writing lessons, (2) the assessment methods employed, (3) the perceived benefits of PBL on students’ writing skills, and (4) the challenges faced during implementation. Data were collected from classroom observations, semi-structured interviews, and document review and were then analyzed qualitatively. The findings revealed that the implementation of PBL followed five key stages: preparation, planning, research, presentation, and evaluation. Writing performance was assessed formatively using an analytical rubric. PBL was found to foster students’ writing development, increase their motivation and engagement, and build confidence. However, implementation challenges such as group management, unequal participation, and time constraints were also reported. These findings suggest that PBL can be a valuable pedagogical tool in EFL writing classrooms, promoting active learning and collaboration. Nonetheless, its success depends on careful instructional planning and strategies for overcoming implementation barriers.